Indicadores integrados de sustentabilidade e análise de decisão multicriterial de barragens subterrâneas no estado do Ceará - França, Francisco Mavignier Cavalcante (2016)
The underground dam is a social technology of low cost and simple process of construction and operation. In the semi-arid zone of Ceara there is potential to build approximately 3,400 underground dams. The central problem of this study is the lack of in-depth knowledge of the degree of sustainability of underground dams of Ceará, in economic, social, environmental and institutional terms. The objective of this thesis is to analyze the sustainability of underground dams, the state of Ceará, as a social technology to living as semi-arid. For this, we used the Dashboard of Sustainability Method by dimension and global, and the Analytic Hierarchy Process to identify the underground dam operating alternative that generates greater benefits to communities. The questionnaires (field research), for the use of Dashboard of Sustainability method, was carried out with 40 farmers, owners of underground dams, located in 11 municipalities of the State of Ceará. The collection of judgments, for the application of Analytic Hierarchy Process applied together 11 experts and / or decision-makers with expertise in underground dams. When using the Dashboard of Sustainability method, which aims to identify the level of performance of sustainable development for indicator by size and global, were selected with the help of principal component analysis, 28 indicators. These indicators, only 36% achieved the level of 700 points, which is the sustainability threshold used in this thesis. None of the four dimensions reached the level of 700 points. The lower performance was with the economic dimension, reaching only 218 points (need for severe attention) when the maximum metric desirable for the model is 1,000 points or at least the threshold of sustainability of 700 points. The overall index, sustainable development (IGDS) of underground dams of Ceara, reached the metric of 538 points, considered an average level of performance and below the sustainability threshold. The selection of dam alternatives, made by AHP, according to the predominant use, showed that the highest priority for investment, to be decided by the public manager is to "underground dam focused on water supply," closely followed by "underground dam focused on agricultural production". The lowest metric was to "dam focused on environmental benefits", with a metric that reached only 33% of the first alternative. Another important finding that deserves reflection, was that farmers (ex-post analysis) have recorded reasonable performance of the environmental dimension indicators, while the expert and decision-makers (analysis ex-ante) have rated the "dam focused on earnings environmental" the third priority, with metric equal to one third of the first alternative.